Rare Tumors in Children and Adolescents - Schneider, Dominik T.; Brecht, Ines B.; Olson, Thomas A.; Ferrari, Andrea; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This is the first book to be devoted exclusively to rare tumors in children and adolescents. The completely revised and updated second edition reflects the significant progress that has been accomplished as a result of intensified international networking, deeper implementation of novel diagnostic tools, and the advent of molecular targeted therapies. Readers will find practical guidance on all aspects of clinical management, including diagnostic workup, multimodal therapy, follow-up, and management of adverse effects. The discussion of differential diagnosis encompasses both frequent and rare tumor types, enabling clinicians to take rare entities into account during diagnostic assessment of childhood tumors. Detailed therapeutic recommendations, developed in an international consensus process, are provided for specific rare tumors. In addition, general issues such as epidemiology, etiology, risk factors, biology and genetics, early detection, and screening are fully covered. The book is written by an international and multidisciplinary group of specialists and will be an important compendium for all pediatric oncologists who care for patients with rare tumors.
1. Introduction: Rare Cancers: a different perspective on oncology -- 2. Epidemiology and etiology of rare cancers -- 3. National and international study groups -- 4. Information and ressources for patients with rare tumors -- 5. Rare tumors of the head and neck -- 6. Rare tumors of the thorax -- 7. Rare tumors of the gastrointestinal tract -- 8. Germ cell tumors and genitourinary tumors -- 9. Rhabdoid tumors -- 10. Rare tunmors of the peripheral nervous system -- 11. Rare tumors of the skin and subcutaneous tissue -- 12. Vascular tumors including Kaposi sarcoma -- 13. Rare mesenchymal tumors -- 14. Tumors of unkown primary site -- 15. Rare tumors as second malignancies.
Keywords: Oncology; Pediatrics; Surgery; Oncology; Pediatrics; Surgery; Neoplasms -- pathology; Rare Diseases -- pathology; Child; Adolescent